2011
DOI: 10.1186/1471-2431-11-64
|View full text |Cite
|
Sign up to set email alerts
|

The role of routine post-natal abdominal ultrasound for newborns in a resource-poor setting: a longitudinal study

Abstract: Background-Neonatal abdominal ultrasound is usually performed in Nigeria to investigate neonatal symptoms rather than as a follow up to evaluate fetal abnormalities which were detected on prenatal ultrasound. The role of routine obstetric ultrasonography in the monitoring of pregnancy and identification of fetal malformations has partly contributed to lowering of fetal mortality rates. In Nigeria which has a high maternal and fetal mortality rate, many pregnant women do not have ante-natal care and not infrequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Cerebral (C) sensor positioned on the forehead (below the hairline) and a renal (R) sensor on the neonate's lower back (right side) between T10 and L2, accurate localization of right kidney performed using ultrasound curvilinear transducer with a frequency ranging between 5 and 7.5 MHz. [17] All infants had general anesthesia induced by incremental concentrations of sevoflurane (2%-4%) with oxygen and 24 gauge intravenous cannula was inserted and secured.…”
Section: Methodsmentioning
confidence: 99%
“…Cerebral (C) sensor positioned on the forehead (below the hairline) and a renal (R) sensor on the neonate's lower back (right side) between T10 and L2, accurate localization of right kidney performed using ultrasound curvilinear transducer with a frequency ranging between 5 and 7.5 MHz. [17] All infants had general anesthesia induced by incremental concentrations of sevoflurane (2%-4%) with oxygen and 24 gauge intravenous cannula was inserted and secured.…”
Section: Methodsmentioning
confidence: 99%
“…The role of the prenatal ultrasound has evolved in its specificity (93-99 %) and sensitivity (14-85 %) for identification of fetal malformations and has partly contributed to the lowering of fetal mortality rates [7,8]. More abnormalities are seen by the third trimester, and a single early scan may miss some fetal anomalies [9]. We performed a retrospective analysis of 41 cases of kidney and urinary tract anomalies diagnosed by antenatal ultrasound during the last 3 years in the Department of Obstetrics and Gynecology, Mansoura University Hospital, Egypt.…”
Section: Discussionmentioning
confidence: 99%
“…Given poor access to antenatal care and screening in resource poor countries, Agunloye et al conducted a study in Nigeria to evaluate the role of routine abdominal US scans in newborns, with the goal of detecting possible abnormalities which may have been missed antenatally (6). They found a 5.9% incidence of genitourinary abnormalities, primarily affecting the kidneys, suggesting that there is some benefit to routine pre-and post-natal screening.…”
Section: Obstetric/gynecologic Ultrasoundmentioning
confidence: 99%
“…They found a 5.9% incidence of genitourinary abnormalities, primarily affecting the kidneys, suggesting that there is some benefit to routine pre-and post-natal screening. While Nigeria has a high maternal and fetal mortality rate and could benefit significantly from routine US screening, investigators identified cost of equipment and lack of skilled personnel as major barriers to implementing this technology (6).…”
Section: Obstetric/gynecologic Ultrasoundmentioning
confidence: 99%
See 1 more Smart Citation